The Southern Literary Messenger, Vol. I., No. 3, November, 1834 - Various; Heath, James E. (Salt Lake City, UT : Project Gutenberg, 2016)
"The Southern Literary Messenger, Vol. I., No. 3, November 1834" by Various is a literary periodical published during the early 19th century. This issue showcases a broad range of topics, as it is dedicated to literature and the fine arts, featuring a historical account of Tripoli and other Barbary States, along with engaging essays and creative works. The content is likely to reflect the cultural and political dynamics of the time, providing readers with insights into both the literary scene and contemporary global issues. At the start of this volume, the publisher outlines the plans for the periodical and appeals to its readers for support to enhance its circulation and quality. The opening article delivers an in-depth examination of the history and current state of Tripoli and the Barbary States, articulating the complexities of their socio-political conditions after a long period of obscurity. It discusses the impact of European powers on these regions, intertwining historical narratives with observations on the human condition, ultimately urging a connection to the shared experiences of civilization and moral duty. (This is an automatically generated summary.)
Release date is 2016-11-11
Produced by Ron Swanson
Keywords: American literature -- 19th century -- Periodicals